2024
DOI: 10.1111/mmi.15231
|View full text |Cite
|
Sign up to set email alerts
|

Functional promiscuity of small multidrug resistance transporters from Staphylococcus aureus, Pseudomonas aeruginosa, and Francisella tularensis

Peyton J. Spreacker,
Andrea K. Wegrzynowicz,
Colin J. Porter
et al.

Abstract: Small multidrug resistance transporters efflux toxic compounds from bacteria and are a minimal system to understand multidrug transport. Most previous studies have focused on EmrE, the model SMR from Escherichia coli, finding that EmrE has a broader substrate profile than previously thought and that EmrE may perform multiple types of transport, resulting in substrate‐dependent resistance or susceptibility. Here, we performed a broad screen to identify potential substrates of three other SMRs: PAsmr from Pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…Several other putative hits identified in the prior screen showed no growth difference for E. coli expressing WT or E14Q PAsmr (Figure S3), demonstrating that not all hits identified based on NADH production show a significant growth phenotype. Compared to previously tested growth in higher ionic strength media (24), growth in nutrient broth also resulted in earlier and more pronounced phenotypic differences between WT and E14Q PAsmr (Figure 2, S1, S2, S4). PAsmr phenotypes for harmane and 18-crown-6 ether in low-ionic strength media are consistent but more pronounced than those in Muller-Hinton Broth (24), suggesting that decreased ability to compensate for ∆pH dissipation may occur in low-ionic strength media.…”
Section: Ecoli Expressing Pasmr Display Substrate Dependent Growth Ef...mentioning
confidence: 58%
See 4 more Smart Citations
“…Several other putative hits identified in the prior screen showed no growth difference for E. coli expressing WT or E14Q PAsmr (Figure S3), demonstrating that not all hits identified based on NADH production show a significant growth phenotype. Compared to previously tested growth in higher ionic strength media (24), growth in nutrient broth also resulted in earlier and more pronounced phenotypic differences between WT and E14Q PAsmr (Figure 2, S1, S2, S4). PAsmr phenotypes for harmane and 18-crown-6 ether in low-ionic strength media are consistent but more pronounced than those in Muller-Hinton Broth (24), suggesting that decreased ability to compensate for ∆pH dissipation may occur in low-ionic strength media.…”
Section: Ecoli Expressing Pasmr Display Substrate Dependent Growth Ef...mentioning
confidence: 58%
“…Compared to previously tested growth in higher ionic strength media (24), growth in nutrient broth also resulted in earlier and more pronounced phenotypic differences between WT and E14Q PAsmr (Figure 2, S1, S2, S4). PAsmr phenotypes for harmane and 18-crown-6 ether in low-ionic strength media are consistent but more pronounced than those in Muller-Hinton Broth (24), suggesting that decreased ability to compensate for ∆pH dissipation may occur in low-ionic strength media. Overall, for compounds tested previously in growth assays, phenotypic results were consistent with growth in E. coli in higher ionic strength media (24), and confirmed that PAsmr confers resistance to the known EmrE substrate, MeTPP + .…”
Section: Ecoli Expressing Pasmr Display Substrate Dependent Growth Ef...mentioning
confidence: 58%
See 3 more Smart Citations